대학부속병원 근무 의사들의 한의학에 대한 인식 - 이은주(Eun Joo Lee); 박한솔(Han Sol Park); 이소영(So Young Lee); 배다정(Da Jung Bae); 이탁근(Tag Gun Lee); 신현규(Hyeun Kyoo Shin) (동의생리병리학회지, 2012)
Since 2010, in general hospital, they can install western medical post, traditional Korean medical post, and dental post. So the environment is made for the Cooperative medical system between traditional Korean medicine(TKM) and western medicine(WM) to be performed. So we found out about how doctors think about TKM and what is needed for TKM & WM cooperative system to work well. When we found out about how recognition changed about TKM during their medical school years and after they became doctors, positive answer increased from 25.6% to 30%, negative answer decreased from 41.9% to 32.0%, severely negative increased from 9.3% to 16%. They changed to positive about TKM after they became doctors. But severely negative also increased. The element they lose faith in TKM is their doubt about the scientific aspects of TKM. On the other hand, severely negative recognition was also raised. 73.8% of respondents thought the most effective treatment of TKM was for myalgia. 33.3% of them answered the chance to encounter TKM was the mass media, indicating its limitation. 60.5% of them considered major reason for negative evaluation of TKM is its non-scientific aspects and only 30.9% said TKM treatment could be recommended to patients at the hospital. Doctors in WM for recognition on TKM is mostly negative and major reason is its non-scientific aspects. As the solution to this problem, scientification of TKM is suggested through research projects. These connections must be resolved to smoothly work interdisciplinary system of TKM and WM.